Aristotelian Rhetoric in Syriac : Barhebraeus, Butyrum Sapientiae, Book of Rhetoric - Watt, John, (Aristoteles Semitico-Latinus ;, 2005)
This volume contains the Syriac text, edited for the first time, of the commentary on Aristotle's Rhetoric by Bar Hebraeus (died 1286) in his Cream of Wisdom. The text is accompanied by an English translation, and the volume also includes an introduction, commentary, and three glossaries (Syriac, Greek and Arabic). Bar Hebraeus' commentary is based on the lost Syriac version of Aristotle's treatise, but the author also drew heavily on the commentary of Ibn Sina (Avicenna). The text therefore provides a unique insight into the nature of that lost version, and also exemplifies the way Bar Hebraeus blended the Aristotle of the Graeco-Syriac translation literature with the more recent philosophy of Ibn Sina.